The Participatory Development Program to Promote Ergonomic Self-Care Competence for Elderly Rice Farmers - Somboonnadee, Woraluk; Srikuta, Phatcharee; Satayavongthip, Bhuddhipong (Ratchaphruek Journal, 2025)
This research aimed to develop a program to promote ergonomic self-care competencies for elderly rice farmers in a participatory manner and to evaluate the results of using the developed program. The program was developed by 15 key informants in Taladkhao Sub-district, Chokchai District, Nakhon Ratchasima Province; representatives of elderly rice farmers, representatives of village public health volunteers, representatives of the local government and civil society and trial the program in a sample of elderly rice farmers of 50 people as experimental group in Taladkhao Sub-district, Chokchai District, and 50 people as control group in Takob Sub-district, Pakthongchai District. Data were analyzed by using frequency, percentage, average, standard deviation, t-test, and content analysis. The results showed that the developed program consisted of 4 activities: 1) Developing knowledge about ergonomics and self-care; 2) Building up competency in ergonomics and self-care; 3) Monitoring and stimulating the development of ergonomics self-care competencies; and 4) Learning and experiences exchange. After evaluation, the results of the trial program indicated that the experimental group had knowledge of the ergonomics of rice farming, self-efficacy, result expectations for health outcomes, ergonomic behaviors in rice farming, and the severity of ergonomics health effects from rice farming in the past 7 days, it was better than before participating in the program. When comparing the results with the control group, the mean score of the experimental group was statistically significantly better than the control group at .05.